A Systematic Review to Identify Screening Tools and Practices that Can Be Used by Children's Rehabilitation Service Providers to Screen Parents' Mental Health. (4th July 2022) - Phoenix, Michelle; Kingsnorth, Shauna; Hamdani, Yani; Ballantyne, Marilyn; Scratch, Shannon E.; Pezzullo, Sam; Reitzel, Meaghan; Albin, Maya; Popov, Nadejda; Kirubainathan, Layana; King, Gillian
ABSTRACT: Background: Parents of children with disabilities often report stress, depression, and anxiety. This review identified screening tools and practices that pediatric rehabilitation service providers can use to screen the mental health of parents of children with disabilities Methods: An interdisciplinary team and patient partner completed the systematic review in which 16, 015 articles were screened and 473 articles were included to i) identify mental health tools that were used with parents, ii) determine the clinical utility of frequently used tools, iii) examine the screening practices used in pediatric rehabilitation contexts Results: 115 screening tools were used to screen parents' mental health. The Parenting Stress Index was used most often. Seven studies reported screening in order to recommend further assessment or supports. Increased awareness, training, resources, and infrastructure are needed to support parents' mental health Discussion: Evidence is needed to guide mental health screening practices in pediatric rehabilitation and determine their effectiveness.